The study on the effects of gamified interactive e-books on students’ learning achievements and motivation in a Chinese character learning flipped classroom - Chen, Chuang; Jamiat, Nurullizam; Mao, Yongchun (Frontiers in Psychology, 2023)
Existing empirical research has demonstrated the positive effects of flipping the classroom to improve student motivation and achievement by flipping in-class learning content to pre-class. However, the flipped classroom approach requires that students be engaged and motivated in the pre-class stage to ensure that the in-class learning activities run smoothly. Previous studies have highlighted the difficulties that students often encounter when trying to learn Chinese characters in Chinese language classes, especially those who are in the early stages of learning the language. Therefore, in this study, a gamified interactive e-book was developed and used in a flipped classroom for Chinese character learning. To evaluate the effectiveness of this approach, a pre-test and post-test control group experimental design was used. The participants were 90 s-grade students from a public primary school in Zhengzhou, China, who were randomly assigned to two experimental groups and one control group: the students who used a gamified interactive e-book in a Chinese character learning flipped classroom (GIEFC group), the students who used a traditional flipped classroom (TFC group), and the students who used a traditional teaching classroom (TTC group). The experimental results indicated that students in the GIEFC group scored higher than those in the TFC and TTC groups in terms of learning achievements and motivation. In addition, the experimental results also demonstrated the positive effects of gamified interactive e-books in flipped classroom learning. Future research could explore a variety of different types of game elements as well as the extension of research to other subjects.